Self-organized Routing For Radial Underwater Networks - Poncela-González, Javier (My University, 2016)
Due to significant propagation delay of acoustic waves in underwater communication, terrestrial routing protocols are not applicable for UWSN. To overcome this problem, some routing protocols have been proposed for UWSN based on the location of the nodes. The routing protocols proposed for UWSN usually require measuring additional parameters, which make the protocol inefficient in terms of energy conservation. Sometimes, also time synchronization among the nodes is required, which is also not an easy task in UWSN. We propose a route initialization mechanism, which avoids these constraints. A path will be formed between all nodes and the gateway, decreasing the forwarding delay and increasing the throughput.
Keywords: Protocolos de comunicaciones; Routing